Patent Publication: Impact of Social Media Influencers on Beauty and Cosmetic Brands in India and Nepal - Mishra, Anjay Kumar; Mishra, Shila; Gautam, Tara Prasad; Chalise, Mahananda (Apex Journal of Business and Management, 2026)
The editorial aims to Illustrate the Impact of Social Media Influencers on Beauty and Cosmetic Brands in India and Nepal based on a published Indian patent with application no. 202641010406 dated on 13/02/2026 could be verified from Intellectual Property India. The beauty industry has seen the rise of influencer marketing as a potent promotional approach in recent years, thanks to the rapid proliferation of digital platforms such as Instagram, YouTube, and Facebook. Reviews, lessons, and endorsements from influential people are becoming increasingly important to consumers when it comes to making purchasing selections. This study examines the ways in which the credibility of influencers, the authenticity of content, and the engagement of audiences all have an impact on the level of brand recognition, trust, and sales performance. According to the findings of the study, influencer-driven marketing is an efficient method for altering customer preferences and enhancing brand visibility in the beauty and cosmetics industry across India and Nepal.